ISOLATION OF ORAL PATHOGENS ASSOCIATED WITH PERIODONTAL CONDITIONS AND EVALUATION OF THE ANTIMICROBIAL EFFICACY OF SELECTED COMMERCIAL DENTIFRICES - Musa, Ramatu Abdulkadir; Ibrahim, Salihu (FUDMA Journal of Sciences, 2026)
Periodontal disease is a polymicrobial inflammatory condition linked to dental plaque accumulation. Dentifrices are commonly used to aid plaque control and may contain antimicrobial agents; however, their effectiveness varies depending on formulation. This study evaluated microorganisms associated with periodontal conditions and assessed the antimicrobial activity of ten commercially available dentifrices. Fifty oral swab samples were collected and processed using standard microbiological techniques. Streptococcus mutans, Escherichia coli, and Candida albicans were isolated and identified through culture and biochemical tests. The antimicrobial efficacy of ten dentifrices was determined using the Kirby–Bauer disc diffusion method. Zones of inhibition were measured in millimeters and analyzed statistically using one-way ANOVA. A total of 58 isolates were recovered, comprising S. mutans (48.28%), C. albicans (31.03%), and E. coli (20.69%). Antimicrobial activity varied among formulations. Dentifrice B showed the highest antibacterial activity against S. mutans (23.6 mm) and E. coli (24.8 mm), while dentifrice J demonstrated the strongest antifungal activity against C. albicans (23.4 mm). Some formulations exhibited no detectable antimicrobial effect. Commercial dentifrices differ significantly in antimicrobial efficacy. Fluoride-containing formulations demonstrated superior antibacterial activity. Further in vivo studies are required to confirm their clinical effectiveness.
Keywords: Periodontal disease; Oral pathogens; Dentifrices; Antimicrobial efficacy; Streptococcus mutans